An age estimation technique and some normal blood values for mountain lions (Felis concolor) - Currier, Mary Jean Pfile, author; Russell, Kenneth R., advisor; Bowling, Rodney A., committee member; Nagy, Julius G., committee member; Schooenveld, Gene D., committee member (Colorado State University. Libraries, 1979)
The objectives of this study were: (1) to devise a method for estimating the ages of individual, wild-caught mountain lions, (2) to identify the normal ranges of various physiological and morphological parameters in the mountain lions, and (3) to determine whether differences in the physiological and morphological parameters measured exist between wild-caught mountain lions captured in south-central Colorado and captive lions in other areas. The age-estimation formula developed for females included the following blood parameters: globulins, blood urea nitrogen, total proteins, percentage monocytes, and zinc; and morphological measurements: gum line recession from the premolars and rear tarsal length. The age-estimation formula developed for males included the following blood parameters: globulins, alkaline phosphatases, and percentage neutrophils; and morphological measurements: gum line recession from the upper canine and total body length. Both formulas had an r2 of about 0.80. Blood, hair, and vibrissae samples; and tooth and body measurements were taken from 46 captive and 31 free-ranging mountain lions. Eight animals were sampled each year for three years, 22 for two years, and 50 only once, for a total of 52 female and 34 male captive lion samplings, and 21 female and 11 male wild lion samplings. The blood samples were evaluated for hematocrit, amount of zinc in the plasma, 18 serum parameters, and white blood cell differentials. The hair and vibrissae samples were stretched until they broke to measure elasticity. Two upper and two lower teeth were measured for gum line recession and measurements of six body characteristics were made. Normal (mean) values and 95 percent confidence intervals for all 38 parameters were determined. The entire 118 samplings were divided into several sets of subgroups and selectively tested for significant differences (P ≤ 0.10) in each of the 38 parameters. Three male mountain lions were raised from age 3 weeks. Eighteen summer and 17 winter blood samples were taken and tested for summer-winter differences. Ten blood and two morphological parameters were significantly different between the wild, and captive, non-kitten mountain lions. Two blood and five morphological parameters were significantly different between female, and male, non-kitten mountain lions. Eight blood and all morphological parameters were significantly different between wild kittens and wild non-kittens. Six blood parameters were significantly different between summer and winter blood collections. Twenty-six parameters (the 12 determined to be significantly different between wild and captive lions were omitted) were initially evaluated for the development of the age-estimation formulas with multiple regression analysis. Of the eight blood parameters found to be significantly different between wild kittens and wild non-kittens, two were included in the female age-estimation formula and three in the male age estimation formula. Winter-summer significant differences were probably not seasonal differences, but for the most part due only to restraint or method of immobilization.
Keywords: Puma; Animals -- Age determination